Masquerade as an Escape from Oneself. Fiodor Stepun’s Considerations on Human Being, Time and Eternity .......... 195 - Lechowska, Marta (Czas w kulturze rosyjskiej, 2019)
MASQUERADE AS AN ESCAPE FROM ONESELF. FIODOR STEPUN’S CONSIDERATIONS ON HUMAN BEING, TIME AND ETERNITYThe aim of the article is philosophical analysis of Fiodor Stepun’s letter to his wife, written on the front of First World War. The subject of the letter is celebration of the  New Year, especially the fundamental feature of the celebration – masquerade. The masquerade is – in frame of Stepun’s conception – cultural manifestation of the human search for eternity. In this way the cultural phenomenon is a sign of human – in fact, tragic, because of being suspended between time and infinity – condition.